Molecular Characterization of Proline Rich Regions in Lens culinaris under Abiotic Stress - Bux, Bhagwan; Kumar, Pankaj; Bharti, Mahesh Kumar; Singh, Jitender (International Journal of Bio-resource and Stress Management, 2022)
The present study attempt was made to isolate and characterized Lens culinaris full length proline rich gene. EST Sequences of proline gene (GT-622346.1) from Lens culinaris was retrieved from Genbank. This sequence was used as query against chickpea. Similarity sequence search has shown up to 90% similarity with EST sequence of chickpea having the Accession No. GR 398344 and up to 85% similarity with EST sequence having Accession No. GT 622346 of Lens culinaris. The positive results were subjected to sequencing and were further in-silico analysis carried out. BLASTp of the lentil sequence showed 98% similarity with Phaseolus vulgaris (accession number-CAJ43592), 97% with Cicer arietinum (accession number-XP004506458), 96% with Medicago truncatula (accession number-Q40375) and 91% similarity with Pisum sativum (accession number-CAB63486). Ten conserved repeats of 180 amino acids each in case of Lens culinaris having the repeat sequence “KPPVEKPPVY” was observed. The sequence was further translated into amino acid sequence and the Interproscan results for proline rich protein in Lens culinaris was found. These findings may help to develop more tolerant lentil crop against drought having a higher potential to satisfy demands for production by increasing the crop productivity.